A comparison of performance metrics for cloth face masks as source control devices for simulated cough and exhalation aerosols - Lindsley, William G; Blachere, Francoise M; Beezhold, Donald H; Law, Brandon F; Derk, Raymond C; Hettick, Justin M; Woodfork, Karen; Goldsmith, William T; Harris, James R; Duling, Matthew G; Boutin, Brenda; Nurkiewicz, Timothy; et al. (medRxiv : the preprint server for health sciences, 2021)
Universal mask wearing is recommended by the Centers for Disease Control and Prevention to help control the spread of COVID-19. Masks reduce the expulsion of respiratory aerosols (called source control) and offer some protection to the wearer. However, masks vary greatly in their designs and construction materials, and it is not clear which are most effective. Our study tested 15 reusable cloth masks (which included face masks, neck gaiters, and bandanas), two medical masks, and two N95 filtering facepiece respirators as source control devices for aerosols ≤ 7 µm produced during simulated coughing and exhalation. These measurements were compared with the mask filtration efficiencies, airflow resistances, and fit factors. The source control collection efficiencies for the cloth masks ranged from 17% to 71% for coughing and 35% to 66% for exhalation. The filtration efficiencies of the cloth masks ranged from 1.4% to 98%, while the fit factors were 1.3 to 7.4 on an elastomeric manikin headform and 1.0 to 4.0 on human test subjects. The correlation coefficients between the source control efficacies and the other performance metrics ranged from 0.31 to 0.66 and were significant in all but one case. However, none of the alternative metrics were strong predictors of the source control performance of cloth masks. Our results suggest that a better understanding of the relationships between source control performance and metrics like filtration efficiency, airflow resistance, and fit factor are needed to develop simple methods to estimate the effectiveness of masks as source control devices for respiratory aerosols.